Chronic obstructive pulmonary disease (COPD) and emergency departments: the impact of attributing a general practitioner - Saraiva, Carolina de Sousa Letras Sales (2019)
With an increasing prevalence of chronic diseases, people are experiencing more emergency episodes. Chronic Obstructive Pulmonary Disease (COPD) will be, by 2020, the third leading cause of death and its acute exacerbations will pose major challenges on primary and secondary health care management. This study uses a database comprising all emergency admissions between 2014 and 2015. A probit model is estimated to assess the impact of different factors on the probability of being a frequent user. Results show it increases (within COPD patients) for men, with 80+ years of age and an assigned General Practitioner. These patients are vulnerable and will need timely access to health care. Accordingly, the creation of health policies, such as the attribution of a general practitioner to these patients, is of crucial importance.